FENOMENA MEMBELI TIRTHA PADA UPACARA NGABEN DI BALI: (Studi di Kabupaten Tabanan) - Girinata, I Made; Giri, I Putu Agus Aryatnaya; Settings I Komang Dian Adi Purwadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The phenomenon of buying tirthas at cremation ceremonies in the Tabanan Regency area is deemed necessary to carry out research, considering that among the community there are pros and cons and even complaints because it is seen as something burdensome. Through this research, it is hoped that we will find the reasons that cause the phenomenon of buying tirtha at the cremation ceremony. The approach used in this research is a phenomenological approach. The data collected comes from primary data and secondary data. Data was collected using techniques: observation, interviews, and document study. Next, it is analyzed using qualitative descriptive and interpretative methods, then the final stage is presenting the research results. The research results show that the reasons for the phenomenon of